Evolution of telemedicine utilization for pediatric urology during the COVID-19 pandemic and beyond: A single center experience - Gan, Zoe S.; Shah, Yash B.; Plachter, Natalie; Weiss, Dana A.; Van Batavia, Jason; Zderic, Stephen A.; Shukla, Aseem R.; Srinivasan, Arun K.; Kolon, Thomas F.; Zaontz, Mark R.; Canning, Douglas A.; Long, Christopher J. (Frontiers in Urology, 2022)
Telemedicine utilization rapidly expanded throughout the COVID-19 pandemic and yielded numerous patient benefits. However, its future remains uncertain, limiting further institutional investments in telemedicine. We aimed to evaluate trends in the volume of telemedicine visits throughout the pandemic and patient factors associated with telemedicine usage to inform the future role of telemedicine in pediatric urology. An IRB-approved registry of pediatric urology outpatient visits was queried from 6/2019-11/2021 at a single institution. Variables of interest included patient demographics, travel distance for care, insurance status, primary visit diagnosis, and visit type (in-person visits, IPVs; or video visits, VVs). IPVs and VVs were further categorized as new patient visits (NPVs), return patient visits (RPVs), and post-operative visits (post-ops). Monthly trends in descriptive variables were summarized. 51,605 pediatric urology outpatient visits occurred during the study period. Patients had a median age of 5 years (IQR 1-11) and were predominantly male (71.6%), white (61.6%), and held private insurance (69%). VVs increased substantially from 0% in February 2020 to 100% in April 2020 and then subsequently declined through November 2021, although total visit volumes were increasing throughout the period. As the pandemic progressed, compared to IPVs, VVs were more likely to have a RPV visit type (80% vs. 50-60%) and longer median travel distance (30+ miles vs. 14 miles). VVs were less frequently covered by subsidized insurance (20-30% vs. 50-70%). In summary, this study found that telemedicine usage has declined since the peak of the COVID-19 pandemic, although its use remains higher than pre-pandemic levels and appears to be associated with RPVs, longer travel distance, and private insurance coverage. Utilization has stabilized as we have emerged from peak pandemic restrictions. Further work is required to elucidate the optimal role of telemedicine and its effects on access to care in pediatric urology.